Pathological mechanisms and novel drug targets in fibrotic interstitial lung disease - Yasuhiko Nishioka; Jun Araya; Yoshiya Tanaka; Atsushi Kumanogoh (BMC, 2024)
Abstract Background Interstitial lung diseases (ILDs) are a diverse group of conditions characterized by inflammation and fibrosis in the lung. In some patients with ILD, a progressive fibrotic phenotype develops, which is associated with an irreversible decline in lung function and a poor prognosis. Main body The pathological mechanisms that underlie this process culminate in fibroblast activation, proliferation, and differentiation into myofibroblasts, which deposit extracellular matrix proteins and result in fibrosis. Upstream of fibroblast activation, epithelial cell injury and immune activation are known initiators of fibrosis progression, with multiple diverse cell types involved. Recent years have seen an increase in our understanding of the complex and interrelated processes that drive fibrosis progression in ILD, in part due to the advent of single-cell RNA sequencing technology and integrative multiomics analyses. Novel pathological mechanisms have been identified, which represent new targets for drugs currently in clinical development. These include phosphodiesterase 4 inhibitors and other molecules that act on intracellular cyclic adenosine monophosphate signaling, as well as inhibitors of the autotaxin-lysophosphatidic acid axis and $$α_v$$ α v integrins. Here, we review current knowledge and recent developments regarding the pathological mechanisms that underlie progressive fibrotic ILD, including potential therapeutic targets. Conclusion Knowledge of the pathological mechanisms that drive progressive fibrosis in patients with ILD has expanded, with the role of alveolar endothelial cells, the immune system, and fibroblasts better elucidated. Drugs that target novel mechanisms hold promise for expanding the future therapeutic armamentarium for progressive fibrotic ILD.